Estimating the role of spatial varietal diversity on crop productivity within an abatement framework: The case of banana in Uganda - Kwikiriza, Norman; Katungi, Enid; Horna, Daniela (International Food Policy Research Institute, 2011)
Increasingly, research has indicated that in more risky production environments, genetic variation within species and within population increases the ability to respond to the increasing challenges of environmental stress. This paper analyses the role of banana variety diversity in reducing yield losses associated with biophysical production constraints in Uganda. A damage abatement framework is applied to enable estimation of the contribution of both direct and indirect inputs to the banana yield per unit of area. Primary data were gathered from 120 households. Results indicate that banana variety diversity contributes positively to reducing yield losses caused by biophysical constraints, particularly pests and diseases, but trade-offs exist. High banana variety diversity also has a significant but negative direct impact on banana yields. These trade-offs imply that while banana variety diversity should be promoted for its risk-reducing effects, its adoption beyond what farmers are practicing will largely depend on their objectives, access to alternative abatement agents, and their ability to bear risk. Given the current banana production environment of limited abatement agents and high biotic stress, enhancing diversity appears to be an important option despite trade-offs.